Improving the Production of Riboflavin by Introducing a Mutant Ribulose 5-Phosphate 3-Epimerase Gene in Bacillus subtilis - Yang, Bin; Sun, Yiwen; Fu, Shouying; Xia, Miaomiao; Su, Yuan; Liu, Chuan; Zhang, Chunzhi; Zhang, Dawei (Frontiers in Bioengineering and Biotechnology, 2021)
Ribulose 5-phosphate (Ru5P) and guanosine 5′-triphosphate (GTP) are two key precursors of riboflavin, whereby Ru5P is also a precursor of GTP. Ribulose 5-phosphate 3-epimerase (Rpe) catalyzes the conversion of ribulose 5-phosphate into xylulose 5-phosphate. Inactivation of Rpe can reduce the consumption of Ru5P, enhancing the carbon flux toward riboflavin biosynthesis. Here we investigated the effect of mutation of rpe and other related genes on riboflavin production, physiological and metabolic phenotypes in Bacillus subtilis LY (BSLY). Introducing single nucleotide deletion (generated BSR) or nonsense mutation (generated BSRN) on the genomic copy of rpe, resulting in more than fivefold increase of riboflavin production over the parental strain. BSR process 62% Rpe activity, while BSRN lost the entire Rpe activity and had a growth defect compared with the parent strain. BSR and BSRN exhibited increases of the inosine and guanine titers, in addition, BSRN exhibited an increase of inosine 5′-monophosphate titer in fermentation. The transcription levels of most oxidative pentose phosphate pathway and purine synthesis genes were unchanged in BSR, except for the levels of zwf and ndk, which were higher than in BSLY. The production of riboflavin was increased to 479.90 ± 33.21 mg/L when ribA was overexpressed in BSR. The overexpression of zwf, gntZ, prs, and purF also enhanced the riboflavin production. Finally, overexpression of the rib operon by the pMX45 plasmid and mutant gnd by pHP03 plasmid in BSR led to a 3.05-fold increase of the riboflavin production (977.29 ± 63.44 mg/L), showing the potential for further engineering of this strain.